Improving seed germination and physiological characteristics of maize seedlings under osmotic stress through potassium nano-silicate treatment - Weisany, Weria; Razmi, Javad; Pashang, Danial (Frontiers in Plant Science, 2023)
Osmotic stress can significantly affect the survival and functioning of living organisms, particularly during vulnerable stages such as seed germination and seedling growth. To address this issue, advanced technologies like nanofertilizers have been developed to improve soil conditions and enhance plant growth in stressed ecosystems due to their multiple effects and efficient consumption. The objective of this study was to investigate the impact of potassium nano-silicate (PNS) on the physiological characteristics of maize seedlings and seed germination under various levels of osmotic stress induced by polyethylene glycol (PEG). The study considered two factors: two levels of PNS concentration (500 and 1000 ppm) and PEG-6000 solution with different osmotic stress levels (-2, -4, -6, and -8 bars). The results demonstrated that the application of PNS at a concentration of 1000 ppm led to increased radicle length and hypocotyl length as well as fresh weight of maize seedlings. Furthermore, PNS at a concentration of 1000 ppm had a more beneficial effect on the germination rate of maize seedlings under osmotic stress compared to 500 ppm. Additionally, the application of PNS under osmotic stress conditions resulted in an increase in various physiological parameters, including protein content, chlorophyll a, chlorophyll b, total chlorophyll content, proline content, and the activity of catalase (CAT) and ascorbate peroxidase (AXPO) enzymes. These findings indicate that the use of PNS can have a positive impact on the physiological characteristics of maize seedlings and seed germination under osmotic stress conditions. Overall, this technology has the potential to enhance crop growth and yield in stressed ecosystems. By improving the survival and function of plants during vulnerable stages, such as seed germination and seedling growth, the application of PNS can contribute to more resilient agricultural practices and promote sustainable food production in challenging environments.